Genome‐wide association study of inhaled corticosteroid response in admixed children with asthma. Issue 6 (15th February 2019) - Hernandez‐Pacheco, Natalia; Farzan, Niloufar; Francis, Ben; Karimi, Leila; Repnik, Katja; Vijverberg, Susanne J.; Soares, Patricia; Schieck, Maximilian; Gorenjak, Mario; Forno, Erick; Eng, Celeste; Oh, Sam S.; et al.
Summary: Background: Inhaled corticosteroids (ICS) are the most widely prescribed and effective medication to control asthma symptoms and exacerbations. However, many children still have asthma exacerbations despite treatment, particularly in admixed populations, such as Puerto Ricans and African Americans. A few genome‐wide association studies (GWAS) have been performed in European and Asian populations, and they have demonstrated the importance of the genetic component in ICS response. Objective: We aimed to identify genetic variants associated with asthma exacerbations in admixed children treated with ICS and to validate previous GWAS findings. Methods: A meta‐analysis of two GWAS of asthma exacerbations was performed in 1347 admixed children treated with ICS (Hispanics/Latinos and African Americans), analysing 8.7 million genetic variants. Those with P ≤ 5 × 10 −6 were followed up for replication in 1697 asthmatic patients from six European studies. Associations of ICS response described in published GWAS were followed up for replication in the admixed populations. Results: A total of 15 independent variants were suggestively associated with asthma exacerbations in admixed populations ( P ≤ 5 × 10 −6 ). One of them, located in the intergenic region of APOBEC3B and APOBEC3C, showed evidence of replication in Europeans (rs5995653, P = 7.52 × 10 −3 ) and was also associated with change in lung function after treatment with ICS ( P = 4.91 × 10 −3 ). Additionally, the reported association of the L3MBTL4 ‐ ARHGAP28 genomic region was confirmed in admixed populations, although a different variant was identified. Conclusions and clinical relevance: This study revealed the novel association of APOBEC3B and APOBEC3C with asthma exacerbations in children treated with ICS and replicated previously identified genomic regions. This contributes to the current knowledge about the multiple genetic markers determining responsiveness to ICS which could lead in the future the clinical identification of those asthma patients who are not able to respond to such treatment.